Endocardial biventricular pacing for chronic heart failure patients: Effect on transmural dispersion of repolarization. Issue 4 (12th June 2019) - Yamin, Muhammad; Yuniadi, Yoga; Alwi, Idrus; Setiati, Siti; Munawar, Muhammad
Abstract: Background and Aim: Conventional epicardial cardiac resynchronization therapy (CRT) can cause fatal arrhythmia associated with increased transmural dispersion of repolarization (TDR). It is unknown whether endocardial biventricular pacing in various locations will decrease TDR and hence the occurrence of fatal arrhythmia. This study aimed to find out the most effective location of endocardial biventricular pacing resulting in the shortest homogenous TDR. Methods: A before‐and‐after study on adult chronic heart failure (CHF) patients undergoing endocardial biventricular pacing in several defined locations. The changes in TDR from baseline were compared among various pacing locations. Results: Fourteen subjects were included with age ranged 36‐74 years old, of which 10 were males. Location revealed the highest post biventricular pacing TDR (113.4 (SD 13.8) ms) was the outlet septum of right ventricle in combination with lateral wall of left ventricle (RVOTseptum‐LVlateral) while the lowest one (106.1 (SD 11.6) ms) was of the right ventricular apex and posterolateral left ventricle (RVapex‐LVposterolateral). Two CRT locations resulted in the most homogenous TDR, that is the right ventricular apex ‐ left ventricular lateral wall (RVapex‐LVlateral, mean difference −9.43; 95% CI (−19.72;0.87) ms, P  = 0.07) and right ventricular apex ‐ left ventricle posterolateral wall (RVapex‐LVposterolateral, mean difference −6.85; 95% CI (−13.93;0.22) ms, P  = 0.056). Conclusion: Endocardial biventricular pacing on right ventricular apex and left ventricular lateral/posterolateral walls results in the most homogenous TDR.